Psychosocial Impact of COVID-19 Pandemic on Patients with End-Stage Kidney Disease on Hemodialysis - Jacqueline Lee; Jennifer L. Steel; Maria‐Eleni Roumelioti; Sarah J. Erickson; Larissa Myaskovsky; Jonathan G. Yabes; Bruce L. Rollman; Steven D. Weisbord; Mark Unruh; Manisha Jhamb (2020)
Background The coronavirus disease 2019 (COVID-19) may have a negative effect on the mental and social health of patients with ESKD on chronic in-center hemodialysis (HD), who have a high burden of psychologic symptoms at baseline and unavoidable treatment-related COVID exposures. The goal of our study was to assess the effect of the COVID-19 pandemic on the psychosocial health of patients on chronic in-center HD. Methods Participants enrolled in the ongoing Technology Assisted Collaborative Care (TĀCcare) trial in Western Pennsylvania and New Mexico were approached for participation in a phone survey in May 2020. Data on the pandemic’s effects on participants’ physical and mental health, symptoms (such as anxiety, mood, loneliness, sleep, and stress), and food and housing security were collected. Results Surveys were completed by 49 participants (mean age 56 years; 53% men, 18% Black, 20% American Indian, and 22% Hispanic). Almost 80% of participants reported being moderately to extremely worried about the pandemic’s effects on their mental/emotional health and interpersonal relationships. More than 85% of the participants were worried about obtaining their dialysis treatments due to infection risk from close contact in the dialysis facility or during transportation. Despite this, 82% of participants reported being not at all/slightly interested in trying home dialysis as an alternative option. Overall, 27% of the participants had clinical levels of depressive symptoms but only 12% had anxiety meeting clinical criteria. About 33% of participants reported poor sleep quality over the last month. Perceived stress was high in about 30% of participants and 85% felt overwhelmed by difficulties with COVID-19, although 41% felt that things were fairly/very often going their way. Conclusions Our study provides preliminary insights into the psychosocial distress caused by the COVID-19 pandemic among a diverse cohort of patients receiving chronic HD who are participating in an ongoing clinical trial.